Puddling Influence on Soil, Rice Development, and Yield - Sharma, P.K.; De Datta, S.K. (Wiley, 1985)
The effects of puddling on soil physical properties, percolation losses of water and nutrients, and nutrient uptake and grain yield of IR36 rice (Oryza sativa L.) in an Andaqueptic Haplaquoll and a Lithic Hapludoll were evaluated in a field experiment. Puddling decreased the bulk densities of both soils in the top 0.1‐m layer by about 30%, but the differences in bulk density between puddled and nonpuddled soil narrowed with time. In the first soil, mechanical strength at 1 d after transplanting (DT) and at 60 DT was the same for both puddled and nonpuddled soils and was <0.3 MPa in the top 0.15‐m layer. In the second soil, it was significantly lower in puddled plots at 1 DT, but the differences between puddled and nonpuddled plots were not significant at 60 DT. Puddling decreased percolation rate by > 70% in the second soil but its effect on percolation rate was negligible in the first. It decreased seasonal water losses by percolation by about 0.03 m in the first soil and by 0.48 m in the second. Puddling decreased significantly the saturated hydraulic conductivities (Ks) of the surface layer in the second soil. In the top 0.15‐m layer, puddling decreased maximum temperatures and diurnal temperature amplitudes in the second soil, but caused no measurable differences in the first. Puddling decreased the redox potential (Eh) of both soils and increased Fe and Mn solubilities. In puddled soil, at the 0.3‐m depth, soil‐solution concentrations of Mn and Fe were higher and those of NH+4‐N, P, K, and Zn comparable to those in nonpuddled soil. The concentration of NO‐3‐N in puddled soil was either comparable to or lower than that in nonpuddled soil. In the first soil, puddling significantly decreased leaching losses of NO‐3‐N; in the second, it decreased leaching losses of NO‐3‐N, NH+4‐N, P, K, and Zn. Puddling significantly increased grain yield in both soils. Total nutrient uptake by rice increased significantly with puddling in both soils. Higher percolation rates did not improve soil productivity, but increased leaching losses of water and plant nutrients. Bulk density and soil strength were the main factors affecting grain yield.